Inflation Dynamics in Asia : Causes, Changes, and Spillovers From China - Osorio Buitron, Carolina (IMF Working Papers; Working Paper ;, 2011)
The perception that Asia's inflation dynamics is driven by idiosyncratic supply shocks implies, as a corollary, that there is little scope for a policy reaction to a build-up of inflationary pressures. However, Asia's fast growth and integration over the last two decades suggest that the drivers of inflation may have changed, and that domestic demand pressures may now play a larger role than in the past. This paper presents a quantitative analysis of inflation dynamics in Asia using a Global VAR (GVAR) model, which explicitly incorporates the role of regional and global spillovers in driving Asia's inflation. Our results suggest that over the past two decades the main drivers of inflation in Asia have been monetary and supply shocks, but also that, in recent years, the contribution of these shocks has fallen, whereas demand-side pressures have started to emerge as an important contributor to inflation in Asia.